2016
DOI: 10.3233/nre-161347
|View full text |Cite
|
Sign up to set email alerts
|

Perspective training to treat anger problems after brain injury: Two case studies

Abstract: BACKGROUND: People with acquired brain injury (ABI) often show increased

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Problems with anger are quite typical after traumatic brain injury (TBI). [1][2][3][4][5] Moreover, these problems differ from those of healthy controls in terms of severity and prevalence. A recent study revealed that people with TBI have elevated levels of anger compared to healthy controls.…”
mentioning
confidence: 99%
“…Problems with anger are quite typical after traumatic brain injury (TBI). [1][2][3][4][5] Moreover, these problems differ from those of healthy controls in terms of severity and prevalence. A recent study revealed that people with TBI have elevated levels of anger compared to healthy controls.…”
mentioning
confidence: 99%
“…The ICAN intervention was developed based on well-known theories of emotion, such as the appraisal theory (Moors et al, 2013) and hostile attribution style theory (Combs et al, 2007;Dodge, 2006;Jeon et al, 2013), which similarly propose that emotions, particularly anger, are largely influenced by the way in which one evaluates the actions of others. As described earlier, empirical research supports these theories in individuals with TBI (Neumann, Sander, Perkins, et al, 2021;Winegardner et al, 2016). The group facilitators were involved in the final refinement of the intervention protocol and procedures.…”
Section: Journal Of Emotion and Psychopathologymentioning
confidence: 95%
“…To address post-TBI anger and aggression that is associated with negative attributions, an intervention (Perspective Training) was created and initially examined as part of a two-person case study (Winegardner et al, 2016). The treatment taught participants to think about and experience situations from other people's perspectives (perspective-taking) as a way to generate alternative explanations and more benign interpretations (or social inferences) of others' actions.…”
mentioning
confidence: 99%
“…23 The evidence for effective theory of mind training following traumatic brain injury is very scarce and limited to the treatment of general communication problems 25 or confined to case reports. 26 Social skills training for patients with traumatic brain injury focuses exclusively on behavior. It is based upon the assumption that patients lack well-defined social skills or knowledge that can be (re)learned.…”
Section: Treatment Of Social Cognition and Emotion Regulationmentioning
confidence: 99%